The disruptive relations between sound and image in Poème Électronique (International Journal on Stereo & Immersive Media, 2019)
This academic paper focuses on the installation art Poème Électronique, which involved the collaboration of a painter and architect (Le Corbusier) and a composer (Edgard Varèse) during the 1958 Brussels World Fair. The idea is to analyse the visual and sound dimensions, created from a combined set of rules, but independently developed by each participant. Based on a detailed and well-structured script written by Le Corbusier, Varèse developed a sound work without respecting the original guidelines. This important disruptive characteristic is structured in the relation between sound and image, and consequently in the interaction with the audience.